Privatizing the democratic peace : policy dilemmas of NGO peacebuilding - Carey, Henry F. 1953- (Houndmills, Basingstoke, Hampshire : New York : Palgrave Macmillan, 2012)
"NGOs have become one of the main instruments in building peace, especially as UN sanctioned peacekeeping missions begin to streamline or withdraw from countries and bilateral peacekeeping sponsored by powerful states. During the last three decades, the UN has relied more and more on NGOs and sub-contractors in peacebuilding. The greater the number of multidimensional challenges and dilemmas that emerge for these NGOs, the more are the sponsoring governments and intergovernmental organizations and host states directly affected by these transitional efforts. Henry F. Carey analyzes the difficult choices, consequences and lessons learned from the UN and foreign governments commissioning NGOs and other subcontractors working on six peacebuilding policy goals: reconciliation, security, human rights, the rule of law, foreign aid, and election monitoring. The study examines the effects of the UN and powerful states increasingly relying on NGO peacebuilding in diverse cases like Bosnia, El Salvador, Nicaragua, Haiti, Liberia, Rwanda, Sierra Leone, Sudan, the Philippines, Chechnya, Iraq, Pakistan, and Afghanistan" --
Includes bibliographical references 266-271 and index.
Keywords: United Nations -- History -- 20th century; United Nations -- History -- 21st century; Peace-building -- History -- 20th century; Peace-building -- History -- 21st century; Non-governmental organizations; POLITICAL SCIENCE / NGOs (Non-Governmental Organizations).; POLITICAL SCIENCE / Peace; POLITICAL SCIENCE / International Relations / Diplomacy